Risk Assessment and Prevention of Venous Thromboembolism in Critically Ill Patients in Tibet: A Prospective Cohort Study with Historical Controls - Qiong J; Gu Y; Dekyi J; Dawa; Tsring P; Zhao M; Wang X; Li G; Liu H (Risk Management and Healthcare Policy)
Ji Qiong,1,* Yanmei Gu,2,* Jampa Dekyi,1 Dawa,1 Phurbu Tsring,1 Min Zhao,1 Xin Wang,2 Guangming Li,2 Haixia Liu2 1Department of Critical Care Medicine, Lhasa People’s Hospital, Lhasa, 850000, People’s Republic of China; 2Department of Critical Care Medicine, Beijing Youan Hospital, Capital Medical University, Beijing, 100069, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haixia Liu, Department of Critical Care Medicine, Beijing Youan Hospital, Capital Medical University, 8 Xi Tou Tiao, You An Men Wai Street, Fengtai District, Beijing, 100069, People’s Republic of China, Tel +86 13521206692, Email liuhx2024hx@163.comObjective: Venous thromboembolism (VTE) is a significant concern in critically ill patients. However, the incidence and risk factors of VTE in high-altitude regions like Tibet remain unclear. This study aimed to assess the effectiveness and safety of standardized anticoagulation therapy in preventing VTE among intensive care unit (ICU) patients in Tibet.Methods: This prospective controlled study included 78 patients in the treatment group receiving low molecular weight heparin (LMWH) and 56 patients in the control group without standardized VTE prophylaxis. VTE incidence, risk factors, and safety outcomes were compared between the two groups. Patients were followed up for a minimum of one week after ICU discharge to assess VTE outcomes.Results: The incidence of VTE was significantly lower in the treatment group (35.9%) compared to the control group (42.9%, p< 0.05). Risk factors for VTE included mechanical ventilation. The most common VTE type observed was deep vein thrombosis (DVT), with pulmonary embolism (PE) occurring less frequently. No significant bleeding events were observed in the treatment group.Conclusion: Standardized LMWH prophylaxis effectively reduces VTE incidence in critically ill patients in Tibet without increasing bleeding risk. Regular risk assessment and appropriate prophylaxis should be implemented in high-altitude ICU settings.Keywords: venous thromboembolism, critical care, thromboprophylaxis, high altitude, Tibet